YIELD OF EARLY POTATOES IN THE CONDITIONS OF WESTERN SERBIA: Early poptato - Poštić, Dobrivoj (Journal on Processing and Energy in Agriculture, 2025)
The goal of the research was to determine the variation in the yield of early potatoes in the conditions of western Serbia. During 2021 and 2022, the experiment was carried out at the site of KO Bogatić, the area of ​​the village of Belotić (65 m above sea level, chernozem), 44˚ 49' N, 19˚ 32' E. The research was set up with three potato varieties: one early (Colomba) and two medium early (Esmee and Memphis).     The analysis of productive traits showed very significant differences (r
Keywords: variety, number of tubers